2022
DOI: 10.1111/issj.12390
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to tourism participation: A case of first‐generation local community service providers

Abstract: Participation in tourism businesses for the local community often comes with various challenges. A better understanding of barriers to tourism development can help manage and smoothen community participation in tourism. Over the past two decades, an effort has been made to understand the barriers to tourism, but the perspective of first-generation community participation is not explored in the existing literature. The current study measures barriers to tourism participation through four parameters, i.e., socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
(89 reference statements)
1
1
0
Order By: Relevance
“…These women should be trained to produce their crafts for commercial purposes. One of our earlier studies (Yaja et al 2022) in this region also showed a favourable attitude towards tourism enterprises from the local community. Despite the fact that tourism as a profession was new to them, all of the professionals involved were first-generation members, and they entered the industry without any socio-cultural dogmas, the local community expressed enthusiasm for tourism and related businesses.…”
Section: Managerial Implicationssupporting
confidence: 52%
“…These women should be trained to produce their crafts for commercial purposes. One of our earlier studies (Yaja et al 2022) in this region also showed a favourable attitude towards tourism enterprises from the local community. Despite the fact that tourism as a profession was new to them, all of the professionals involved were first-generation members, and they entered the industry without any socio-cultural dogmas, the local community expressed enthusiasm for tourism and related businesses.…”
Section: Managerial Implicationssupporting
confidence: 52%
“…According to the literature assessment, a holistic understanding of the theoretical and scholarly reinforcement of dark tourism related researches is rare. To understand the foundations, structural features and trends of dark tourism, this present research adopts an approach which is evaluative and relational in nature (Yaja, et al, 2023;Benckendorff & Zehrer, 2013). The findings of this study reflect that there has been a significant growth in dark tourism research since the year 2013.…”
Section: Discussionmentioning
confidence: 81%
“…As a result, the development of tourism products and services at the local level is hampered. And this lack of awareness is reported as a barrier to tourism development (Stone & Stone, 2011;Yaja et al, 2023a). However, questions remain on how such barriers can be removed and through what medium, as well as how to make locals understand tourism projects and plans, particularly in new tourist destinations.…”
Section: Literature Reviewmentioning
confidence: 99%